Comparative two time-point proteome analysis of the plasma from preterm infants with and without bronchopulmonary dysplasia - Magdalena Zasada; Maciej Suski; Renata Bokiniec; Monika Szwarc-Duma; Maria Katarzyna Borszewska-Kornacka; Józef Madej; Beata Bujak-Giżycka; Anna Madetko-Talowska; Cecilie Revhaug; Lars O. Baumbusch; Ola D. Saugstad; Jacek Józef Pietrzyk; et al. (BMC, 2019)
Abstract Background In this study, we aimed to analyze differences in plasma protein abundances between infants with and without bronchopulmonary dysplasia (BPD), to add new insights into a better understanding of the pathogenesis of this disease. Methods Cord and peripheral blood of neonates (≤ 30 weeks gestational age) was drawn at birth and at the 36th postmenstrual week (36 PMA), respectively. Blood samples were retrospectively subdivided into BPD(+) and BPD(−) groups, according to the development of BPD. Results Children with BPD were characterized by decreased afamin, gelsolin and carboxypeptidase N subunit 2 levels in cord blood, and decreased galectin-3 binding protein and hemoglobin subunit gamma-1 levels, as well as an increased serotransferrin abundance in plasma at the 36 PMA. Conclusions BPD development is associated with the plasma proteome changes in preterm infants, adding further evidence for the possible involvement of disturbances in vitamin E availability and impaired immunological processes in the progression of prematurity pulmonary complications. Moreover, it also points to the differences in proteins related to infection resistance and maintaining an adequate level of hematocrit in infants diagnosed with BPD.